Recurrent Hyperinflations and Learning - Marcet, Albert; Nicolini, Juan P (American Economic Review, 2003)
We use a model of boundedly rational learning to account for the observations of recurrent hyperinflations in the 1980’s. In a standard monetary model we replace the assumption of full rational expectations by a formal definition of quasi-rational learning. The model under learning matches some crucial stylized facts observed during the recurrent hyperinflations experienced by several countries in the 1980’s remarkably well. We argue that, despite being a small departure from rational expectations, quasi-rational learning does not preclude falsifiability of the model, it does not violate reasonable rationality requirements, and it can be used for policy evaluation.